Performance of gelatin films reinforced with cloisite na+ and black pepper essential oil loaded nanoemulsion - Saranti, Tascila F. da S. [UNESP]; Melo, Pamela T. S. [UNESP]; Cerqueira, Miguel A.; Aouada, Fauze A. [UNESP]; de Moura, Marcia R. [UNESP] (MDPI, 2021)
The concern about consuming eco-friendly products has motivated research in the development of new materials. Therefore, films based on natural polymers have been used to replace traditional polymers. This study consists of a production of films based on gelatin reinforced with black pepper essential oil-loaded nanoemulsions and Cloisite Na+ . The films were characterized by water vapor permeability, mechanical and thermal properties, surface contact angle, X-ray diffraction and scanning electron microscopy. It was observed that the films containing the nanoemulsion have higher permeability values and an increase in their mechanical resistance. The addition of nanoclay contributed to an increase in the surface hydrophobicity of the film and an increase in the tensile strength, at break, by about 150%. The addition of essential oil nanoemulsions led to an increase in thermal stability. The presence of clay dispersion contributed to the formation of a surface that was slightly rougher and grainier. The addition of the black pepper essential oil nanoemulsion resulted in an increase in porosity of the gelatin matrix. Through X-ray diffraction analysis, it was possible to conclude that both the polymeric gelatin matrix and the essential oils nanoemulsion are intercalated with the clay dispersion.
Keywords: Biopolymer packaging; Black pepper nanoemulsion; Mechanical properties; Nanocomposite films